2013
DOI: 10.1056/nejmoa1202851
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics as Part of the Management of Severe Acute Malnutrition

Abstract: BACKGROUND Severe acute malnutrition contributes to 1 million deaths among children annually. Adding routine antibiotic agents to nutritional therapy may increase recovery rates and decrease mortality among children with severe acute malnutrition treated in the community. METHODS In this randomized, double-blind, placebo-controlled trial, we randomly assigned Malawian children, 6 to 59 months of age, with severe acute malnutrition to receive amoxicillin, cefdinir, or placebo for 7 days in addition to ready-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
243
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(271 citation statements)
references
References 35 publications
14
243
2
3
Order By: Relevance
“…15 In that study, amoxicillin significantly reduced the risk of treatment failure (by 24%) and death (by 36%), as compared with placebo. The authors concluded that antibiotics should continue to be used routinely in areas where kwashiorkor and HIV infection are prevalent.…”
Section: The New England Journal Of Medicinementioning
confidence: 89%
See 2 more Smart Citations
“…15 In that study, amoxicillin significantly reduced the risk of treatment failure (by 24%) and death (by 36%), as compared with placebo. The authors concluded that antibiotics should continue to be used routinely in areas where kwashiorkor and HIV infection are prevalent.…”
Section: The New England Journal Of Medicinementioning
confidence: 89%
“…In Malawi, cefdinir, but not amoxicillin, was associated with increased weight gain, as compared with placebo. 15 Our study has several key limitations. First, we assumed a likelihood of nutritional recovery of 80%, which was not achieved, and we cannot rule out the possibility that amoxicillin had a protective effect of 12% or a harmful effect of 1% on nutritional recovery.…”
Section: The New England Journal Of Medicinementioning
confidence: 91%
See 1 more Smart Citation
“…antimalarial treatment for malaria and metronidazole for gastrointestinal infections and infestations. [7,8,19,25] Correction of micronutrient deficiencies Vitamin and mineral deficiencies are common in malnutrition. Supplementation (Table 2) should be given for at least 2 weeks.…”
Section: Treatment Of Infectionmentioning
confidence: 99%
“…In the last 60 years, they have become a mainstay of the physician's arsenal for fighting bacterial infections in humans, and deaths from such infections have become much less common, at least in countries where antibiotics and good health care are available. Recently it has also been found that antibiotic compounds can be of great utility in treating severe malnutrition [2][3]. Less well-known among the general public are the uses of antibiotic compounds in plant agriculture, in aquaculture, for therapy and prophylaxis in veterinary medicine, and for growth promotion of animals, mainly cattle and poultry [4][5].…”
Section: Introductionmentioning
confidence: 99%